2019
DOI: 10.1158/1078-0432.ccr-18-3442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mucosal Melanoma Whole-Genome Landscapes Reveals Clinically Relevant Genomic Aberrations

Abstract: Purpose: Unlike advances in the genomics-driven precision treatment of cutaneous melanomas, the current poor understanding of the molecular basis of mucosal melanomas (MM) has hindered such progress for MM patients. Thus, we sought to characterize the genomic landscape of MM to identify genomic alterations with prognostic and/or therapeutic implications. Experimental Design: Whole-genome sequencing (WGS) was performed on 65 MM samples, including 63 paired tumor blood samples and 2 matched lymph node metastases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
144
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(164 citation statements)
references
References 45 publications
17
144
1
2
Order By: Relevance
“…On the focal level, KIT, CCND1, CDK4, NOTCH2 amplification, CDKN2A/2B, and PTEN deletion were recurrently seen, in line with previous findings reported by others (Newell et al, ; Zhou et al, ). Noteworthy, amplification of CDK4/CCND1 was also more frequent in patients lacking common driver mutations in cutaneous melanomas (Cancer Genome Atlas, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the focal level, KIT, CCND1, CDK4, NOTCH2 amplification, CDKN2A/2B, and PTEN deletion were recurrently seen, in line with previous findings reported by others (Newell et al, ; Zhou et al, ). Noteworthy, amplification of CDK4/CCND1 was also more frequent in patients lacking common driver mutations in cutaneous melanomas (Cancer Genome Atlas, ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we did not observe the concurrence of NOTCH2 and NRAS amplification as previously reported (Garman et al, ) despite the fact that both genes are located nearby on 1p. Lastly, NOTCH2 amplification was exclusive to acral melanomas in our data, although it has previously been reported in mucosal melanomas (Newell et al, ; Zhou et al, ), which may be attributed to the limited cohort size.…”
Section: Discussioncontrasting
confidence: 77%
“…Malignant tumors are characterized by uncontrolled cell growth, which is mainly due to the dysregulated expression of cancer driver genes that regulate cell proliferation and differentiation. This includes gain of function mutations of oncogenes and functional deletion alterations of tumor-suppressor genes, or disabling of genome maintenance genes (Masuda and Kuwano, 2019;Zhou et al, 2019). Many studies have reported that RBPs show dysregulated expression in various human cancers (Dong et al, 2019;Soni et al, 2019;Velasco et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We used 601 cases with WES data [11][12][13][15][16][17] for discovery, and 18 with WES data 18,23 and 91 with WGS data [18][19][20][21][22] for validation. We also compared our canine findings to those published for the corresponding human cancers 3,4,[24][25][26][27] . The study is described below.…”
Section: Introductionmentioning
confidence: 99%